Адміністративно-правове регулювання відносин у сфері праці в контексті соціальної політики держави - Остапенко, Леонід Олексійович (Національний університет "Львівська політехніка", 2021)
У дисертації в процесі комплексного аналізу правового регулювання відносин у сфері праці, а також проблемних питань адміністративно-правового регулювання, на основі міжнародного і національного загального, галузевого законодавства, нормативно-правових актів та інших правових документів, вироблено та запропоновано рекомендації науково-теоретичного і законодавчого змісту, що сприяють реалізації державної політики України у сфері праці. Визначено, що в регулюванні відносин у сфері праці адміністративноправова характеристика політики держави є лише фрагментарною, особливо це стосується правових основ і реалізації сучасних напрямів державної політики у регулюванні правових відносин, що пов’язані із зайнятістю і працевлаштуванням населення та його соціальним забезпеченням. Обґрунтовано, що державна політика України щодо адміністративноправового регулювання відносин у сфері праці є результатом розвитку і соціальнотрудових, і адміністративно-правових відносин, які позитивно впливають на розвиток наявних та появу нових за змістом підходів у розумінні та поясненні змісту і призначення адміністративно-правового регулювання відносин у сфері праці. Наголошено, що в Україні використання норм адміністративного права є одним з основних правових інструментів не лише в діяльності органів публічного управління, але й у регулюванні соціально-трудових відносин. Зазначено, що шляхом консенсусу, соціального партнерства формується, закріплюється та забезпечується трудоправова поведінка між сторонами (суб’єктами) у сфері праці. В диссертации в процессе комплексного анализа правового регулирования отношений в сфере труда, а также проблемных вопросов административноправового регулирования, возникающих в сфере труда на основе международного и национального общего, отраслевого законодательства, нормативно-правовых актов и других правовых документов, выработаны рекомендации научно теоретического и законодательного содержания относительно государственной политики Украины в рамках административноправового регулирования отношений в сфере труда. Определено, что в регулировании отношений в сфере труда административно-правовая характеристика политики государства является лишь фрагментарной, особенно это касается правовых основ и реализации направлений государственной политики в регулировании правовых отношений, связанных с занятостью и трудоустройством населения и его социальноым обеспечением. Обоснованно, что государственная политика Украины по административно-правовому регулированию отношений в сфере труда является результатом развития как социально-трудовых, так и административно-правовых отношений, что положительно влияет на развитие имеющихся и появление новых по содержанию подходов в понимании и объяснении содержания и назначения административно-правового регулирования отношений в сфере труда. Отмечено, что сегодня в Украине использование норм административного права является одним из основных правовых инструментов не только в деятельности органов публичного управления, но и в регулировании социальнотрудовых отношений. Определено, что путем консенсуса, социального партнерства формируется, закрепляется и обеспечивается трудоправовое поведение между сторонами (субъектами) в сфере труда. In the process of complex analysis of legal regulation of labor relations, as well as problematic issues of administrative and legal regulation, on the basis of international and national common, sectoral legislation, regulations and other legal documents, the recommendations of scientific, theoretical, and legislative content are made and suggested in the dissertation research. By logical, linguistic, semantic, and philosophical analysis the following concepts are considered in the dissertation: «administrative and legal regulation», «state policy», «employment», «control», «employee», «employer», «social dialogue» and others, which allowed determining their general and special features. Along with this, it is noticed that in labor law for a meaningful description of its conceptual and categorical apparatus, the mechanism of legal regulation of social and labor relations, there are no studies of administrative and legal nature that affect the regulation of relations in the field of labor. It is determined that in the regulation of labor relations the administrative and legal characteristic of state policy is only fragmentary, especially in the legal framework and implementation of modern policies on the regulation of legal relations related to employment, hiring and social security of the population. At the same time, the dissertation focuses on the fact that for the administrative and legal regulation of relations in the field of labor it is necessary to use public administration bodies, which are authorized for this activity in accordance with current national legislation. The state policy of Ukraine on administrative and legal regulation of labor relations, using methodological tools, was determined as the result of the development of both social-labor and administrative-legal relations, which positively affect the development of existing and the emergence of new approaches to understanding and explaining the content and purpose of administrative and legal regulation relations in the field of labor. It is determined that the undoubted influence on the state policy of Ukraine in the field of labor have theories that stimulate the development of relations related to employment and hiring, the use of social dialogue in the system of contractual relations in the field of labor. It is emphasized that today in Ukraine the use of rules of administrative law is one of the main legal instruments not only in the activities of public administration bodies but also in the regulation of the most important for society and state social-labor relations. In modern science, there are still ongoing discussions on defining the place and content of administrative and legal policy of the state in the regulation of labor relations. Thus, this issue is particularly relevant, because the subject of legal regulation relationsin the field of laborshould be considered in both broad and narrow dimensions, filling their content with the regulation of rules ofinternational labor law as well as rules of common and intersectoral national law. At the same time, it is important to define the mechanism of administrative and legal regulation of relations in the field of labor. It is the norms of administrative law, which are enshrined in its sources, that are closely connected with the norms of labor law and other branches of national law. It is noticed that the reproduction and combination of the basic principles of administrative and labor law are based on the principles that, being enshrined in the Constitution of Ukraine, are reflected in the draft Labor Code of Ukraine, which will contribute to proper regulation of labor relations. Ukrainian state policy and its influence on the regulation of labor relations, occupying a special place among other directions of its implementation, is quite voluminous, which requires the allocation of only part of the legal aspects related to relations in the field of labor. For the settlement of relations in the field of labor, it is obligatory to consolidate the legal status of the employee and the employer, who are the main subjects of social and labor relations. The protection of their rights, freedoms and legitimate interests in the field of labor cannot have a unipolar dimension and be enshrined in law. Through consensus, social partnership, labor law behavior between the parties (subjects) in the field of labor is being formed, established and ensured. For the violation of labor legislation that legal liability comes, which does not have a sufficient amount of legal protection of relations in the field of labor. This especially applies to the consolidation in the Code of Ukraine on Administrative Offenses of liability for: unreasonable refusal to enter into a collective agreement; violation or non-fulfillment of obligations under the collective agreement; evasion of the received requirements of employees, as well as participation in conciliation procedures and bringing the perpetrators to justice for its violation.
Административно-правовое регулирование отношений в сфере труда в контексте социальной политики государства
Administrative legal regulation of relations in the area of labor in the context of state social policy
Keywords: адміністративно-правове регулювання; відносини у сфері праці; державна політика; заробітна плата; контроль; механізм адміністративноправового регулювання; нагляд; найманий працівник; роботодавець; соціальний діалог; административно-правовое регулирование; отношения в сфере труда; государственная политика; заработная плата; контроль; механизм административно-правового регулирования; надзор; наемный работник; работодатель; социальный диалог; administrative and legal regulation; relations in the field of labor; state policy; wages; control; mechanism of administrative and legal regulation; supervision; employee; employer; social dialogue; 342.9:[331.1.:316.334.3] (477) (043.5)